Phonology of the Qur'an: Al-Nabr and Its Practice in the Qur'an - Wahidi, Ridhoul; Thonthowi, Thonthowi (Taqaddumi: Journal of Quran and Hadith Studies, 2025)
Qur'anic phonology is the study of the sound and pronunciation of the sacred text of the Qur'an. One important aspect of this phonology is al-nabr, which refers to the emphasis of the voice in the pronunciation of the verses of the Qur'an. This emphasis not only serves to clarify meaning, but also has aesthetic and spiritual implications in the recitation of the Qur'an. The practice of al-nabr in the Qur'an involves other sciences such as ashwāt, tajweed and makhraj, which provide guidance on how each letter and syllable should be pronounced correctly. This research is a library research using one of the research work steps of ashwāt science. It explores the ways in which al-nabr is applied in the rules of Arabic and its application in the Qur'an. By understanding the phonology of the Qur'an, one can appreciate the linguistic beauty and depth of meaning contained in the Qur'an. Through descriptive analysis, this article contributes to the treasures of ulumul Qur'an, especially the field of ashwāt science and the urgency of al-nabr in the study of the Qur'an.